PENDIDIKAN HUKUM PEREMPUAN SEBAGAI UPAYA PEMBERDAYAAN PEREMPUAN - Endang Widuri (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
One kind of education that has strategic value to empowerment effort is through law education. The method is givingknowledge with information; education; training and motivation. formal law formal education can form and also placing woman on â€œlink andmatchâ€ concept, in the meaning that human resources determine its existence, as embodiment of Section 27 article (2) UUD 1945. Throughthis concept, we hope women can participate as formulator of law rule and development, so we can reform women image that have beenformed by social and cultural structure of society. Therefore, they will obtain fairer portion based on humanity value, as noted on HumanRights Contract